A systematic mapping study of value-based software engineering - Salleh, Norsaremah; Mendes, Fabiana; Mendes, Emilia (IEEE, 2019)
Integrating value-oriented perspectives into the principles and practices of software engineering is critical to ensure that software development and management activities address all key stakeholders’ views and also balance short-and-long-term goals. This is put forward in the discipline of Value-Based Software Engineering (VBSE). In this paper, a mapping study of VBSE is detailed. We classify evidence on VBSE principles and practices, research methods, and the research types. This mapping study includes 134 studies located from online searches, and backward snowballing of references. Our results show that VB Requirements Engineering (22%) and VB Planning and Control (19%) were the two principles and practices mostly investigated in the VBSE literature, whereas VB Risk Management, VB People Management and Value Creation (3% respectively) were the three less researched. In terms of the research method, the most commonly employed method is case-study research. In terms of research types, most of the studies (28%) proposed solution technique(s) without empirical validation.